Implementasi Musalsal Arabiy Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Siswa Kelas Xii Ponpes Raudhatul Mutaallmin - Khairil Anwar; Doni Sastarawan; M. Ari Wibowo; Ferdinan Agraha; Abu Ayyub (Al Mufid, 2023)
The application of Arabic learning today has many difficulties, both from the components of Maharah Al Lughawiyah and Anashirul Lughah, this happens because of the lack of discussion related to strategies, models, learning methods that are in accordance with learning Arabic which is Ajnabiy. One of the components of anashirul lughah that has a lot of problems is mufrodat, this is because mufradat is the main capital to learn more about sentence structure and other elements in language and with mufradat one can more easily learn Maharah Lughawiyah.The difficulty of understanding mufradat is felt by almost all Arabic learners because mufradat in Arabic does not always lead to one meaning, this makes all Arabic learners need to understand more broadly about the meaning, form and context in the use of a vocabulary.To overcome the problem of understanding mufradat, Arabic language education experts provide strategies, methods and special learning media for non-Arab Arabic learners (lighairi nathiqina biha) and one of them is a serial Arabic learning video (Musalsal Arabiy). The result of the analysis of the results of the community service activities that we carried out was an increase in students' understanding of the Arabic language mufradat. The mistakes that occurred before the service was carried out have not happened again.This increasing understanding can be seen from the students' ability to apply the mufradat in Musalsal Arabiy, this concludes that the implementation of Musalsal Araby to improve students' understanding of mufradat is very effective.